2017
DOI: 10.1016/j.pedobi.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Plant litter functional diversity effects on litter mass loss depend on the macro-detritivore community

Abstract: A better understanding of the mechanisms driving litter diversity effects on decomposition is needed to predict how biodiversity losses affect this crucial ecosystem process. In a microcosm study, we investigated the effects of litter functional diversity and two major groups of soil macro-detritivores on the mass loss of tree leaf litter mixtures. Furthermore, we tested the effects of litter trait community means and dissimilarity on litter mass loss for seven traits relevant to decomposition. We expected mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 103 publications
2
22
0
1
Order By: Relevance
“…A loss or change of decomposer diversity and species composition is likely to alter decomposition dynamics (Hättenschwiler and Gasser, 2005;Heemsbergen, 2004), but its extent and consequences remain difficult to predict (García-Palacios et al, 2016a;Hooper et al, 2005). The majority of studies has analysed the effect of different litter types on decomposition (Patoine et al, 2017) and has shown a mean positive effect of leaf litter species diversity on litter mass loss across biomes (Handa et al, 2014). Nielsen et al (2011) explored the relationship between soil fauna and ecosystem functions relevant for C cycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A loss or change of decomposer diversity and species composition is likely to alter decomposition dynamics (Hättenschwiler and Gasser, 2005;Heemsbergen, 2004), but its extent and consequences remain difficult to predict (García-Palacios et al, 2016a;Hooper et al, 2005). The majority of studies has analysed the effect of different litter types on decomposition (Patoine et al, 2017) and has shown a mean positive effect of leaf litter species diversity on litter mass loss across biomes (Handa et al, 2014). Nielsen et al (2011) explored the relationship between soil fauna and ecosystem functions relevant for C cycling.…”
Section: Introductionmentioning
confidence: 99%
“…In 11 out of 15 studies, they reported a positive relationship between soil fauna species richness and decomposition. Yet, the role of soil fauna on litter decomposition, including not only taxonomic but also functional or phylogenetic metrics, remains mostly unknown (Patoine et al, 2017), especially in urban ecosystems (Schwarz et al, 2017), were environmental conditions and management practices can be profoundly different compared with rural areas (Gaston et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to functional diversity effects, we expected the CWM and variance of certain functional traits to affect litter mass loss (Table 1) (hypothesis 3). For instance, as found in a microcosm study using the same litter mixtures (Patoine et al, 2017), more rapid decomposition was expected for mixtures characterized by high nutrient content, low concentration of defensive compounds (tannins and phenolics), and low leaf stability/strength (thickness and toughness). We expected the variance of nutrient-related traits (leaf N content, leaf C:N, litter C:N) to increase litter mass loss, as diverse mixtures would provide detritivores with complementary food sources to fulfill their nutritional needs (Vos, van Ruijven, Berg, Peeters, & Berendse, 2013).…”
Section: Introductionmentioning
confidence: 55%
“…Similarly, a few other studies also found that FD effects on litter decomposition in mixtures were not significant (Frainer, Moretti, Xu, & Gessner, 2015;Tardif & Shipley, 2015). Partly, inconsistent findings may be due to different litter traits being considered in previous studies as well as temporal dynamics in the decomposition process, and the varying role of litter traits during different stages of litter decomposition (Patoine et al, 2017;Ristok et al, 2017). To exemplify these interactions, a laboratory study that used the same litter mixtures as presented here (i.e., based on the BIOTREE-FD site design) found a positive effect of litter FD on decomposition, but only for a given time period of the experiment, with the effect disappearing at later stages of the experiment (Patoine et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation